Clinical findings of 21 previously unreported probands with HNRNPU‐related syndrome and comprehensive literature review. Issue 7 (22nd April 2020) - Durkin, Anna; Albaba, Shadi; Fry, Andrew E.; Morton, Jenny E.; Douglas, Andrew; Beleza, Ana; Williams, Denise; Volker‐Touw, Catharina M.L.; Lynch, Sally A.; Canham, Natalie; Clowes, Virginia; Straub, Volker; et al.
Abstract: With advances in genetic testing and improved access to such advances, whole exome sequencing is becoming a first‐line investigation in clinical work‐up of children with developmental delay/intellectual disability (ID). As a result, the need to understand the importance of genetic variants and its effect on the clinical phenotype is increasing. Here, we report on the largest cohort of patients with HNRNPU variants. These 21 patients follow on from the previous study published by Yates et al. in 2017 from our group predominantly identified from the Deciphering Developmental Disorders study that reported seven patients with HNRNPU variants. All the probands reported here have a de novo loss‐of‐function variant. These probands have craniofacial dysmorphic features, in the majority including widely spaced teeth, microcephaly, high arched eyebrows, and palpebral fissure abnormalities. Many of the patients in the group also have moderate to severe ID and seizures that tend to start in early childhood. This series has allowed us to define a novel neurodevelopmental syndrome, with a likely mechanism of haploinsufficiency, and expand substantially on already published literature on HNRNPU‐related neurodevelopmental syndrome.